A new species of patch-nosed snake (Colubridae: Salvadora Baird and Girard, 1853) from Oaxaca, Mexico - Hernández-Jiménez, Carlos Alberto; Flores-Villela, Oscar; Campbell, Jonathan Atwood (Zootaxa, 2019)
A new species of snake of the genus Salvadora from Oaxaca, Mexico, is described. This taxon was confused with S. intermedia in previous taxonomic descriptions. It is characterized by lacking a pale vertebral stripe and by having incomplete dorsolateral stripes that do not reach the posterior part of the body, which is typical of congeners; by having both dorsolateral stripes separated each other by five to six scale rows on anterior part of body; and other scalation characters as well as the number maxillary teeth. The importance of this snake and its conservation is discussed.